Assessment of lettuce quality during storage at low relative humidity using Global Stability Index methodology - Ansorena, Maria Roberta (2012)
During postharvest, lettuce is usually exposed to adverse conditions (e.g. low relative humidity) that reduce the vegetable quality. In order to evaluate its shelf life, a great number of quality attributes must be analyzed, which requires careful experimental design, and it is time consuming. In this study, the modified Global Stability Index (GSI) method was applied to estimate the quality of butter lettuce at low relative humidity during storage discriminating three lettuce zones (internal, middle, and external). The results indicated that the most relevant attributes were: the external zone - relative water content (RWC), water content (WC), ascorbic acid (AA), and total mesophilic counts (TMC); middle zone - RWC, WC, total chlorophyll (TC), and AA; internal zone - RWC, bound water, WC, and TMC. A mathematical model that takes into account the GSI and overall visual quality for each lettuce zone was proposed. Moreover, the Weibull distribution was applied to estimate the maximum vegetable storage time which was 5, 4, and 3 days for the internal, middle, and external zone, respectively. When analyzing the effect of storage time for each lettuce zone, all the indices evaluated in the external zone of lettuce presented significant differences (p < 0.05). For both, internal and middle zones, the attributes presented significant differences (p < 0.05), except for WC and TC.